(untitled) (Altre Modernità, 2020)
Neuroscience has offered confirmation that perception of reality does not correspond to reality. The mind is a very effective tool of falsification, because it builds "virtual scenarios" so persuasive that they are interpreted by human beings for "reality". It has been known since ancient times that words have power over reality and philosophical disciplines have often dealt with the relationship between language and reality. Suggestion is based on a particular form of communication, traditionally used in care, that includes a set of techniques for manipulating expectations and perceptions. In many human activities the suggestion reached a high level of complexity and has been widely applied; main areas are advertising, economic choice and political vote. For over a century, however, medicine, in search of scientific foundations, has neglected the role of suggestion in the clinical field. The authors illustrate some historical paths of suggestion in medical context and an overview of its presence, sometimes not recognized and not studied, in various areas of the current clinic practice.